যাদের সাফল্যে আলোকিত বাংলাদেশ - কিবরিয়া, শুভ (ঢাকা : সময় প্রকাশন, 2012)
Collection of interviews given by some well-known personalities from Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Celebrities -- Bangladesh; Celebrities -- Bangladesh -- Interviews